2024
DOI: 10.1096/fj.202302491r
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal triglyceride transfer protein is necessary to maintain lipid homeostasis and retinal function

Catharina R. Grubaugh,
Anuradha Dhingra,
Binu Prakash
et al.

Abstract: Lipid processing by the retinal pigment epithelium (RPE) is necessary to maintain retinal health and function. Dysregulation of retinal lipid homeostasis due to normal aging or age‐related disease triggers lipid accumulation within the RPE, on Bruch's membrane (BrM), and in the subretinal space. In its role as a hub for lipid trafficking into and out of the neural retina, the RPE packages a significant amount of lipid into lipid droplets for storage and into apolipoprotein B (APOB)‐containing lipoproteins (Blp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 105 publications
0
0
0
Order By: Relevance
“…Another study showed that RPE microsomal triglyceride transfer protein (MTP), encoded by the MTTP gene, is critical for apoB-containing lipoprotein synthesis and assembly but is not directly involved in plasma lipoprotein metabolism, suggesting that RPE-specific MTP expression is necessary to establish and maintain retinal lipid homeostasis and visual function [52].…”
Section: Retinal Pigmented Epithelium (Rpe)mentioning
confidence: 99%
“…Another study showed that RPE microsomal triglyceride transfer protein (MTP), encoded by the MTTP gene, is critical for apoB-containing lipoprotein synthesis and assembly but is not directly involved in plasma lipoprotein metabolism, suggesting that RPE-specific MTP expression is necessary to establish and maintain retinal lipid homeostasis and visual function [52].…”
Section: Retinal Pigmented Epithelium (Rpe)mentioning
confidence: 99%